O SISTEMA AQÜÍFERO GUARANI - SAG - Rebouças, Aldo da Cunha; Amore, Luiz (Águas Subterrâneas, 2002)
The Guarani Aquifer System GAS consists of Triassic-Jurassic eolian-fluvio-lacustrine sandstones confined by Upper Jurassic- Late Cretaceous basalt flows. It covers about 1,195,500 km2 - 839,800 km2 in Brazil; 225,500 km2 in Argentine; 71,700km2 in Paraguay and 58,500 km2 in Uruguay - and is the largest transboundary confined aquifer system in the World. Althought the region might be well supplied with surface water resources, GAS countries currently encouter a range of water problems which have the potential to become much worse. Groundwater resources may be important as a source of irrigation water, water supplies, base flows to rivers, and in contributing to wetland water balance and ecology. The major policy considerations that emerged from the examination of GAS countries are that groundwater use should be managed both from the economic efficiency point of view and from the environmental point of view by safeguarding water potential and quality, mainly. Research should be an integral part of groundwater policy to reduce lack of information and to develop cost-effective technical solutions to groundwater pollution problems. The management objective for GAS resources should be long-term efficiency. This means that its quantity and quality should be maintained at an economically, socially and environmentally optimal level, taking into account the long-term uncertainties and the real long-term costs of controls on its use, protection and treatment.